Climate and conflict vulnerability mapping of Northern, Northwestern, Eastern and Uva provinces of Sri Lanka - Dissanayaka, Sujeewa; Eriyagama, Nishadi; Fernando, K.; Azmy, N.; de Alwis, T.; Perera, M.; Muthuwatta, Lal; Abeywardana, H. R.; Morugama, S.; de Silva, Sanjiv; Vinopavan, K. (International Water Management Institute, 2025)
This study examines climate and conflict vulnerability across the Northern, Northwestern, Eastern, and Uva provinces of Sri Lanka, focusing on how climatic and socio-economic factors collectively shape community resilience. It integrates environmental exposure with social and economic dimensions to identify areas where multiple stressors intersect and may influence local stability and well-being. A Climate and Conflict Vulnerability Index was developed using six categories: economic capacity, social resources, personal well-being, demographic factors, climate exposure, and climate sensitivity drivers. Using factor analysis and spatial mapping at the Divisional Secretariat level, the study identifies variations in vulnerability across regions. Districts such as Trincomalee, Jaffna, and Puttalam were found to have relatively higher combined vulnerability, reflecting both environmental pressures and socio-economic challenges. Further analysis in Puttalam District explored localized issues related to water availability, livelihoods, and drought impacts, complemented by stakeholder consultations to validate and contextualize the results. The findings highlight that a combination of climatic variability, resource dependence, and livelihood sensitivity influence the adaptive capacity of communities.